Structure and Biodiversity of Rhodolith Seabeds: A Special Issue - Fernando Tuya (Diversity, 2020)
Rhodolith seabeds function as ‘ecosystems engineers’, which globally provide a range of ‘ecosystem services’. However, knowledge on the structure, composition and distribution of rhodolith seabeds is still lacking. This Special Issue comprises six articles, addressing specific questions of rhodolith seabeds, and covering a wide range of topics. Two papers provide new large-scale information on the presence, structure and distribution of rhodolith beds at two southern hemisphere areas, in particular continental shelfs off South Africa and Brazil. Another two studies contributed to the discovery on new algal species from rhodolith beds, including Sporolithon franciscanum, a new rhodolith-forming species from Brazil, and the small benthic alga Schizocladia ischiensis. In terms of associated fauna, the taxonomic composition and patterns of abundance of decapod crustaceans are described in another article, including the description of a depth-partitioning in the abundance of juveniles and adults of the crab Nanocassiope melanodactylus. Rhodoliths are often present in fossilized deposits, so we can track changes in their presence with climate fluctuations. High temperatures during the Eocene and widespread oligotrophic conditions are finally connected with low abundances of rhodolith beds at mid and high latitudes, despite a larger presence at equatorial regions.